Penapisan Tekanan Darah dalam Upaya Pencegahan Sindrom Metabolik pada Kelompok Usia Dewasa di Wilayah Krendang, Jakarta Barat - Paskalis Andrew Gunawan; Alexander Halim Santoso; Fransisca Iriani Rosmala Dewi; Mario Abdiwijoyo; Edwin Destra (STIKes Ibnu Sina Ajibarang, 2025)
Metabolic syndrome is health condition that include hypertension, hyperglycemia, central obesity, and dyslipidemia, which significantly increase the risk of cardiovascular disease and type 2 diabetes. Blood pressure is one of the main components of metabolic syndrome, where elevated blood pressure serves as an early indicator of serious risk for complications. Routine blood pressure screening in the adult population plays a critical role in the early detection of hypertension and in preventing the progression of metabolic syndrome. This activity aims to raise awareness and understanding among adults about the risks of hypertension and the importance of blood pressure control through routine screening and education on healthy lifestyles. The results show that periodic blood pressure screening is effective in identifying individuals with early-stage hypertension, enabling timely preventive interventions. The education provided successfully enhanced participants' understanding of healthy lifestyles as a preventive measure against hypertension and metabolic syndrome. The conclusion of this activity underscores that blood pressure screening in the adult population is a strategic measure to reduce the risk of complications from metabolic syndrome and hypertension.